Ewolucja myśli polityczno-państwowej Józefa Piłsudskiego oraz jej wpływ na myśl społeczną i dokonania Drugiej Rzeczypospolitej - Bosiacki, Adam (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article is an attempt to provide a comprehensive overview of the political thought of Józef Piłsudski 1867–1935, regarded without reservation as the highest political authority of the Second Polish Republic and the most important figure in the regaining of independence by Poland after 1918. Paradoxically, an analysis of his views as a whole is yet to be carried out, with scholars focus ing mainly on facts or fragments of views or criticism of various phenomena in inter-war Poland in Piłsudski’s thought. The author of the article analyses Piłsudski’s well-known socialist leanings, the concept of the primacy of the state over other public institutions, Piłsudski’s attitude to the most important phenomena after taking over power and his responsibility for the various distortions of Poland’s political system after 1926. He points not only to the concept of systemic reforms but also to the political doctrine conservatism of this figure, the concept of social solidarity and social equ-ilibrium, constitutional propositions formulated a posteriori in line with Piłsudski’s views as well as Piłsudski’s legacy. This legacy is also one of the most important aspects of his political doctrine, even despite the numerous negative phenomena affecting the political and legal philosophy of the post-May camp of inter-war Poland.
Keywords: Piłsudski, Józef (1867-1935); myśl polityczna II Rzeczypospolitej; demokracja parlamentarna; autorytaryzm; system prawny II Rzeczypospolitej Polskiej